Enhanced immunogenicity of the tuberculosis subunit Rv0572c vaccine delivered in DMT liposome adjuvant as a BCG-booster. (May 2022) - Mao, Lirong; Xu, Lifa; Wang, Xiaochun; Xing, Yingru; Wang, Jian; Zhang, Yanpeng; Yuan, Wei; Du, Jianpeng; Shi, Zilun; Ma, Jilei; Zhang, Jingyan; Zhang, Xiaohan; et al.
Abstract: COVID-19 has affected the progress made in the prevention and treatment of tuberculosis (TB); hence, the mortality of tuberculosis has risen. Different strategies-based novel TB vaccine candidates have been developed. This study identifies strategies to overcome the limitations of Bacille Calmette-Guérin (BCG) in preventing latent infection and reactivation of TB. The latency antigen Rv0572c was selected based on the mechanism of interaction between Mycobacterium tuberculosis and its host. The rRv0572c protein was used to stimulate whole blood samples derived from patients with clinically diagnosed active TB (ATBs) or latent TB infections (LTBIs) and healthy control (HCs) donors, confirming that this protein can be recognized by T cells in patients with TB, especially LTBIs. C57BL/6 mice were used to investigate the immunogenicity of the rRv0572c protein emulsified in the liposome adjuvant dimethyldioctadecylammonium [DDA], monophosphoryl lipid A [MPLA], trehalose-6, 6′-dibehenate [TDB] (DMT). The results demonstrated that rRv0572c/DMT could boost BCG-primed mice to induce antigen-specific CD4 + T cell production and generate functional T cells dominated by antigen-specific CD8 + T cells. The rRv0572c/DMT vaccine could also trigger limited Th2 humoral immune responses. These findings suggest that rRv0572c/DMT is a potential subunit vaccine candidate that can be used as a booster vaccine for BCG. Highlights: BCG has limitations against latency tuberculosis and reactivation of tuberculosis. The Rv0572c/DMT subunit vaccine could make up the deficiency of BCG. The spread of tuberculosis was effectively controlled by the Rv0572c/DMT subunit vaccine.